You times the x and y by 3 good luck
Answer:
x=47
Step-by-step explanation:
Answer:
25.13
Step-by-step explanation:
C=2πr=2·π·4≈25.13274cm
Answer:
1. 9
2. 9
3. 101
Step-by-step explanation:
hope it helps:)
Top:
x / (x + 1) - 1 / x
= [x^2 - (x +1)] / x(x+1)
= (x^2 - x - 1 ) / x (x+1)
Bottom:
x / (x + 1) + 1 / x
= [x^2 + (x +1)] / x(x+1)
= (x^2 + x + 1 ) / x (x+1)
Now you have:
(x^2 - x - 1 ) / x (x+1)
----------------------------
(x^2 + x + 1 ) / x (x+1)
= (x^2 - x - 1 ) / x (x+1) * x (x+1) / (x^2 + x + 1 )
= (x^2 - x - 1 ) /(x^2 + x + 1 )
Answer:
x^2 - x - 1
---------------------
x^2 + x + 1